2013
DOI: 10.1002/nag.2175
|View full text |Cite
|
Sign up to set email alerts
|

Second‐order work analysis for granular materials using a multiscale approach

Abstract: SUMMARY It has been established that the second‐order work criterion is a general necessary condition for all instabilities by divergence in rate‐independent granular materials. The relation between the values of discrete second‐order work at the intergranular contact point level and its global macroscopic value is recalled at the beginning of this paper. Then, the basic purpose of the paper is tackled by an analysis of the main features of second‐order work criterion in relation with the granular microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…It was found that the direction of the shear band (around 60°) was the direction of the interparticle second‐order work having the maximum negative value (Figures C and A), demonstrating that the micro slip lines have degenerated into shear band. The simulation results are consistent with those obtained by the discrete element method simulations of a drained biaxial compression test on a dense sample by Nicot et al, which demonstrated that the multiscale approach does explain the localised failure of granular assemblies.…”
Section: Analyses Of the Influence Of Microstructural Instabilities Osupporting
confidence: 88%
“…It was found that the direction of the shear band (around 60°) was the direction of the interparticle second‐order work having the maximum negative value (Figures C and A), demonstrating that the micro slip lines have degenerated into shear band. The simulation results are consistent with those obtained by the discrete element method simulations of a drained biaxial compression test on a dense sample by Nicot et al, which demonstrated that the multiscale approach does explain the localised failure of granular assemblies.…”
Section: Analyses Of the Influence Of Microstructural Instabilities Osupporting
confidence: 88%
“…Complementary to the previous section, the particular role played by rattlers in mitigating plastic strain development can be examined analytically and qualitatively using the micro-formulation of the second-order work introduced for granular materials (Nicot et al, 2007;Hadda et al, 2013). In this section the contact scale necessary condition to observe the vanishing of the second-order work (Nicot and Darve, 2006a;Nicot et al, 2013) is revisited in terms of rattlers influence to provide an analytical proof of the conjecture formulated in Section 2.5. This section is kept qualitative on purpose but a quantitative assessment of the role played by rattlers directly at the contact scale is proposed in Appendix A through DEM simulations.…”
Section: A Contact Scale Explanation For the Stabilizing Role Played mentioning
confidence: 97%
“…However, it must be emphasized that this force chain deconfinement does not seem to be the triggering mechanism, as was shown in the case of an incremental stress loading corresponding to a nega-tive second-order work [34]. Indeed, for classical stresscontrolled directional analysis under axisymmetric conditions, the vanishing of the second-order work is usually observed for loading directions corresponding to a macroscopic dilation [13,34,41]. At the microscale, this dilation results in some contact loss.…”
Section: Mesoscale Mechanismsmentioning
confidence: 94%